Concurrent validity of intelligence assessments in children with developmental disabilities in an Asian setting: Comparison of the Kaufman brief intelligence test - Second edition with the Wechsler Intelligence Scales - Alison S.M. Cheng; Jolene Q.J. To; Noor Hafizah Wahianuar; Yiong Huak Chan; Kalyani Vijaykumar Mulay (Elsevier, 2024)
Background: This study was carried out to compare the concurrent validity of the Kaufman Brief Intelligence Test - Second Edition (KBIT-2) with that of two Wechsler Intelligence Scales (Wechsler Intelligence Scale for Children - Fifth Edition (WISC-V) and the Wechsler Preschool and Primary Scale of Intelligence - Fourth Edition (WPPSI-IV)) in an Asian setting. Methods: A retrospective study reviewed the medical records of 101 children with developmental disorders who were being followed up at a tertiary child development unit. Pearson product moment correlation coefficients were calculated between the KBIT-2 and Wechsler assessment scores. Simple regression analysis was used to calculate standard errors of estimation to assess the accuracy of predicting Wechsler scores using KBIT-2 scores. Results: A strong positive correlation was observed between KBIT-2's Intelligence Quotient (IQ) Composite and WISC-V's Full-Scale IQ (FSIQ) scores (r = 0.722, p < 0.01). KBIT-2 IQ composite scores showed a moderately strong positive correlation with WPPSI-IV FSIQ scores (r = 0.648, p < 0.01). Simple regression analysis showed that KBIT-2 scores tended to underestimate or overestimate the Wechsler scores, with the highest variability seen in KBIT-2's Non-Verbal IQ and Wechsler's Fluid Reasoning Index scores (error limits: -53.1 to 39.7). Conclusion: Our study demonstrates that KBIT-2 has good concurrent validity when compared to other IQ tests such as the Wechsler scales, and it suggests that KBIT-2 is a good screening tool for assessing intelligence in a group of children with developmental disabilities. Further studies are needed to determine whether KBIT-2 can be used for the purpose of diagnostic decision-making or special education program placement.